KENDALA PENGEMBANGAN DESA WISATA MUNGGU, KECAMATAN MENGWI, BADUNG - Sunarjaya, I Gede; Antara, Made; Oka Prasiasa, Dewa Putu (JURNAL MASTER PARIWISATA; Volume 04, Nomor 02, Januari 2018, 2018)
Badung Regent Regulation No. 47 year 2010 on the establishment of the tourism village area in Badung Regency has determined that Badung regency has eleven tourism villages. Munggu Tourism Village is one of the eleven tourist villages. The development of Munggu Tourism Village still faces many obstacles since its adoption in 2010. The purpose of this study is to assess and formulate concepts and plans that will be the basis for the development of tourism village viewed from the constraints of the development of the tourism village, stakeholder participation as well as programs to develop tourism village of Munggu. Data in the research were collected through qualitative observation, in depth interviews, questionnaires, and documentation. The data were obtained through purposive sampling for the local communities and the tourist. The article concludes that the the absence of master plan of tourism village and minimum sdupport from tourism stakeholders have caused problems in speeding up development of Munggu tourism village.